In the business of gendered violence: the private shelter discourse in Sweden - Lauri, Marcus; Lauri, Johanna (Critical and radical social work, 2024)
For-profit companies have begun competing with women’s shelters for ‘clients’ trying to escape violence. Using discourse theory, this study examines how 20 private shelters describe their business. The analysis shows that private shelters describe themselves as: (1) having a broad expertise and target group: (2) being able to tend to the individual needs of any client; and (3) being highly available and flexible. We understand this as an expression of a neoliberal market discourse and as a way to differentiate themselves from women’s shelters. This may put pressure on women’s shelters to provide similar ‘inclusion’, availability and flexibility. Furthermore: (4) private shelters contribute to shaping a desirable neoliberal subject, that is, a self-reliant woman; and (5), by articulating needs as individual and inherently mundane, they lean more towards ‘providing accommodation’ than addressing the particularities of (gendered) violence.